Assessment and evaluation of requirements elicitation techniques using analysis determination requirements framework - Besrour, S. (Institute of Electrical and Electronics Engineers Inc., 2014)
Numerous requirements engineering methods have been proposed to improve the quality of requirements documents and to increase customer satisfaction with the final product. However, the choosing between various techniques may be confusing and puzzling. Therefore, this paper aims to present an empirical study to assess requirement analysis techniques, highlight their key features, strength and limitations. The empirical study results show a high competitiveness between requirement engineering techniques and slight score differences among them. Statistics shows that Interview technique is the uppermost obtained score among all techniques, followed by JAD and Brainstorming technique. Â© 2014 IEEE.